Structural insights into human serum albumin-mediated prostaglandin catalysis - Yang, Jinsheng (Cold Spring Harbor Laboratory Press, 2002)
Previous studies have shown that many arachidonic acid metabolites bind to human serum albumin (HSA) and that the metabolism of these molecules is altered as a result of binding. The present study attempted to gain insights into the mechanisms by which prostaglandins bound to subdomain 2A of HSA are metabolized by catalytic processes. The breakdown of the prostaglandin 15-keto-PGE(2) to 15-keto-PGA(2) and 15-keto-PGB(2) in the presence of wild-type HSA and a number of subdomain 2A mutants was examined using a previously validated spectroscopic method which monitors absorbance at 505 nm. The species examined using this method were wild-type HSA, K195M, K199M, F211V, W214L, R218M, R218P, R218H, R222M, H242V, R257M, and bovine serum albumin. Previous studies of HSA-mediated catalysis indicated that the breakdown of HSA-bound prostaglandins results from an alkaline microenvironment in the binding site. Our results show that the catalytic breakdown of HSA-bound 15-keto-PGE(2) to 15-keto-PGB(2) results from two specific processes which are modulated by specific amino acid residues. Specifically, some amino acid residues modulate the rate of step 1, the conversion of 15-keto-PGE(2) to 15-keto-PGA(2), while other residues modulate the rate of step 2, the conversion of 15-keto-PGA(2) to 15-keto-PGB(2). Some residues modulate the rate of steps 1 and 2. In total, while our results support the involvement of certain basic amino acid residues in the catabolism of HSA-bound 15-keto-PGE(2), our data suggest that metabolism of HSA-bound prostaglandins may be a more complex and specific process than previously thought.